Effects of bovine Herpesvirus Type 5 on development of in vitro-produced bovine embryos - Silva-Frade, C. [UNESP]; Martins, A. [UNESP]; Borsanelli, A. C. [UNESP]; Cardoso, T. C. [UNESP] (Elsevier B.V., 2010)
Bovine (Bos indicus) herpesviruses have been associated with reproductive disease. Type 1, the most studied species, is best known for its reproductive and respiratory effects. Type 5 (BoHV-5) has been detected in bull semen and aborted fetuses but not in oocytes and embryos. This study consisted of three experiments that evaluated (1) BoHV-5-infected oocytes matured in medium with fetal bovine serum (BoHV-FES) or polyvinyl alcohol (BoHV-PVA) and fertilized by noninfected sperm; (2) noninfected oocytes fertilized by BoHV-5-infected sperm; and (3) infection of presumptive zygotes by BoHV-5. Each treatment involved nine drops of 15 to 20 oocytes. Infection with BoHV-5 was detected by polymerase chain reaction and in situ hybridization assay, and fertilization capacity and embryonic development were assessed using in vitro culture. Experimentally induced infection was obtained in all experiments, and vertical transmission of BoHV-5 by gametes was confirmed. The cleavage rate was reduced (P = 0.0201) in BoHV-FBS (80.4 +/- 8.9%; mean +/- SD) compared with that of noninfected oocytes (89.9 +/- 6.5%); neither differed from BoHV-PVA (87.3 +/- 7.1%), and the resulting embryo production rate was not significantly different among groups. Rates of cleavage (87.5 +/- 7.5% vs. 92.2 +/- 5.5%, control vs. infected) and development of embryos (41.7 +/- 9.9% vs. 44.3 +/- 7.7% to morula/blastocyst/expanded blastocyst [M/B/EB] and 39.6 +/- 10.3% vs. 40.8 +/- 9.2% to blastocyst/expanded blastocyst/hatching blastocyst [B/EB/HB] stages) were not compromised by infected sperm (P = 0.1462, P = 0.5402, and P = 0.8074, respectively). However, presumptive zygotes directly infected 1 d after fertilization produced a lower number (P = 0.0140 to M/B/EB and P = 0.002 to B/EB/HB stages) of in vitro-produced embryos (31.6 +/- 4.6 vs. 25.0 +/- 5.5 and 31.6 +/- 4.6 vs. 20.2 +/- 5.4; control vs. infected). In conclusion, BoHV-5 infected gametes and was transmissible to the embryo during in vitro development. As zygotes infected 1 d after fertilization had compromised development, BoHV-5 has the potential to be a pathogen with economic consequences. (C) 2010 Published by Elsevier B.V.
Keywords: BoHV-5; Cattle; Embryos; ISH; PCR